The Perception-Reality Gap in Digital Marketing: Measuring Social Media's True Influence on Nepal's Cold Drink Consumer Choices - Chand, Prakash Bahadur; Awasthi, Keshab Raj; Pandey, Dipak Raj (Quantitative Economics and Management Studies, 2025)
This study investigates the influence of social media marketing, including advertisements, influencer endorsements, and user-generated content, on consumer preferences and purchasing behavior for cold drinks in Nepal. Using a descriptive research design with purposive sampling (N=384), the study collected data through structured questionnaires targeting active social media users aged 18-35. Descriptive analysis revealed that social media advertisements had the highest perceived impact (Mean=38.98), followed by influencer marketing (Mean=27.09). However, correlation and regression analyses painted a different picture: while a weak but significant link existed between influencers and user-generated content (r=.134, p<.01), none of the social media variables significantly predicted actual consumer preferences (p>.05, R²=.005). The findings suggest a notable disconnect between perceived and real influence, implying that factors like price, taste, and convenience may outweigh digital marketing effects in Nepal’s cold drink market. The study challenges the assumed dominance of social media in shaping consumer behavior, particularly in emerging markets, and calls for more nuanced, locally tailored marketing strategies. Future research should incorporate behavioral tracking, cross-platform comparisons, and longitudinal designs to better understand the gap between online engagement and actual purchasing decisions. These insights are critical for marketers aiming to optimize digital campaigns in price-sensitive, culturally distinct markets like Nepal.